Remarkable difference in structural relaxation dynamics of conventionally prepared bulk glass and vapor-deposited thin films - Málek, Jiří; Svoboda, Roman (American Institute of Physics, 2024)
"The structural relaxation dynamics of conventionally prepared bulk glass of N,N '-bis(3-methylphenyl)-N,N '-diphenyl-benzidine (TPD) was measured by differential scanning calorimetry. The calorimetric data were quantitatively described in terms of the Tool-Narayanaswamy-Moynihan (TNM) model. The TNM parameters were evaluated using a combination of linearization and non-linear optimization methodologies: h*/R = 109.5 kK, ln(A/s) = -321, beta = 0.37, x = 0.64. In addition, the TNM phenomenology was used to describe recently reported normalized thickness data of stable and aged thin TPD films measured by ellipsometry. The structural relaxation was found to proceed at a markedly higher rate in these thin films prepared by the physical vapor deposition compared to that of conventional bulk glass. This feature appears to be associated with the significantly narrower distribution of relaxation times (beta congruent to 0.8) observed for stable thin film in ""as-deposited"" form with uniquely dense molecular packing. Interestingly, very similar attributes of the relaxation kinetics were also found in the aged thin film with a previously erased thermal history associated with the deposition."
Pozoruhodný rozdíl v dynamice strukturální relaxace konvenčně připraveného objemového skla a tenkých filmů připravených odpařováním
Keywords: enthalpy relaxation; thermal-stability; recovery; history; entalpická relaxace; tepelná stabilita; historie; sklo; film